1993
DOI: 10.1111/j.1476-5381.1993.tb13731.x
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete reversal of β‐adrenoceptor desensitization in human and guinea‐pig cardiomyocytes by cyclic nucleotide phosphodiesterase inhibitors

Abstract: 1 The decreased response to P-adrenoceptor stimulation seen in heart failure may be related to a defect in cyclic AMP production. The inotropic effects of the selective phosphodiesterase (PDE) III inhibitors, SK&F 94120 and SK&F 94836, and the non-selective PDE inhibitor, 3-isobutyl-1-methylxanthine (IBMX), alone and when combined synergistically with isoprenaline, were studied in control and P-adrenoceptor-desensitized ventricular myocytes.2 Myocytes isolated from noradrenaline-treated guinea-pigs had a reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…The present study is the first to suggest that these changes can be attributed directly to sympathetic overactivation and abnormalities in signal transduction, rather than to diffuse myocardial damage and contractile dysfunction. More importantly, some prior studies have demonstrated a reduced inotropic response to 3-isobutyl-1-methylxanthine (IBMX), a nonselective PDE inhibitor, after chronic β-AR activation [18,35]. However, the daily dose of β-AR agonist employed in these studies was approximately 200 times greater than that used in this study, and basal contractile function was not defined [18,35].…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The present study is the first to suggest that these changes can be attributed directly to sympathetic overactivation and abnormalities in signal transduction, rather than to diffuse myocardial damage and contractile dysfunction. More importantly, some prior studies have demonstrated a reduced inotropic response to 3-isobutyl-1-methylxanthine (IBMX), a nonselective PDE inhibitor, after chronic β-AR activation [18,35]. However, the daily dose of β-AR agonist employed in these studies was approximately 200 times greater than that used in this study, and basal contractile function was not defined [18,35].…”
Section: Discussionmentioning
confidence: 50%
“…More importantly, some prior studies have demonstrated a reduced inotropic response to 3-isobutyl-1-methylxanthine (IBMX), a nonselective PDE inhibitor, after chronic β-AR activation [18,35]. However, the daily dose of β-AR agonist employed in these studies was approximately 200 times greater than that used in this study, and basal contractile function was not defined [18,35]. Hence, the reduced PDE inhibitor responsiveness could be ascribed to generalized cardiac changes secondary to necrotic or apoptotic damage, well known to occur at high doses of β-AR agonists [3,8].…”
Section: Discussionmentioning
confidence: 99%
“…A high selectivity for PDE3 inhibition seems not to be a prerequisite for PDE inhibitor to exhibit contractile effect since potent inotropic responses could be elicited by agents like theophylline and IBMX which non-selectively inhibit PDE1, PDE2, PDE3 and PDE4 isoenzymes [65,112,163,164,167,176,177]. Likewise, both PDE3 selective and non-selective PDE inhibitors are able to potentiate "-ARmediated inotropic responses [55,163,164,169,178,179].…”
Section: Blockade Of Adenosine Receptorsmentioning
confidence: 93%
“…Likewise, both PDE3 selective and non-selective PDE inhibitors are able to potentiate "-ARmediated inotropic responses [55,163,164,169,178,179]. In failing myocardium, a reduction of inotropic responses to "-AR agonists is reversed by co-administration of PDE inhibitor [55,57,164,169].…”
Section: Blockade Of Adenosine Receptorsmentioning
confidence: 97%
See 1 more Smart Citation